Micro-Computed Tomography as a complementary tool for histopathological diagnosis of oral soft tissue lesions – Proof of concept - Lazar Kats; Yankel Gabet; Uzi Shpunt; Marilena Vered (PLoS ONE, 2025)
Background Accurate diagnosis of oral soft tissue lesions is critical for effective treatment, yet conventional histopathological examination, the gold standard, faces limitations. These include two-dimensional (2D) visualization and malorientation, which can obscure critical diagnostic features, like epithelial-connective tissue interfaces. Micro-computed tomography (µCT) offers a non-destructive, high-resolution three-dimensional (3D) imaging alternative to address these challenges. Still, its use for soft tissue visualization is limited. We tested a method with specific radio-opaque staining and µCT scanning settings to visualize oral soft tissue biopsies as a proof of concept. Methods Biopsies from 12 patients with different oral mucosa lesions were stained with Lugol’s iodine, scanned at 3µm resolution with 70kV energy, and the resulting volumes were compared to histopathological sections by specialists in oral radiology and oral pathology. Results µCT produced 2D images with tissue architecture comparable to hematoxylin and eosin (H&E)-stained sections, distinguishing epithelium, connective tissue, and keratin, while 3D reconstructions revealed topographic details, such as ulceration depth and vascular patterns, unattainable in histopathology. Conclusions These findings highlight µCT potential as a complementary diagnostic tool, enhancing topographic rendering while preserving tissue integrity. Standardized protocols and broader validation, particularly for precancerous and malignant lesions, are essential for clinical adoption, promising improved diagnostic accuracy in oral pathology.